“WE STOPPED DREAMING”: JULIE OTSUKA’S (UN)TOLD STORIES OF PICTURE BRIDES - CHEVEREȘAN, Cristina (Studia Universitatis Babeș-Bolyai Philologia, 2019)
“We Stopped Dreaming”: Julie Otsuka’s (Un)Told Stories of Picture Brides. Focusing on Julie Otsuka’s acclaimed 2011 novel, The Buddha in the Attic, this paper will investigate the picture bride phenomenon as a multilayered trade of lives, identities, emotions and expectations, drawing a vivid picture of the protagonists’ subjection to exploitation, abuse, discrimination and deceit. REZUMAT. ”Am încetat să visăm”: Julie Otsuka și poveștile (ne)spuse ale mireselor prin corespondență. Pornind de la elogiatul roman din 2011 al scriitoarei Julie Otsuka, Buddha din podul casei, lucrarea de față va analiza fenomenul mireselor prin corespondență drept comerț cu vieți, identități, emoții și așteptări, oferind un viu portret al confruntării protagonistelor cu exploatarea, abuzul, discriminarea și înșelătoria. Cuvinte cheie: visul American, voce colectivă, imigrație, japonezi, legislație, căsătorie, mirese prin corespondență, context socio-istoric.